Mechanochemical synthesis of pillar[5]quinone derived multi-microporous organic polymers for radioactive organic iodide capture and storage - Kecheng Jie (Nature Portfolio, 2020)
Incorporation of supramolecular macrocycles into porous organic polymers can increase uptake of guest molecules through host−guest interactions. Here the authors report a pillar[5]quinone derived multi-microporous organic polymer, which show a superior performance in radioactive iodomethane capture and storage.